"Hacking and information disorder: the weaponization of leaking". - Di Salvo, Philip (Critical Studies in Media Communication, 2025)
This essay examines the dual role of leaks as both a journalistic tool and a vehicle for propaganda, with a focus on state-sponsored hack-and-leak operations. While leaks have traditionally served investigative journalism, the rise of cyberattacks and disinformation has redefined their role within the broader context of information disorder. Hack-and-leak operations leverage authentic documents obtained through cyberattacks, releasing them tactically to shape media narratives, foster doubt, and undermine targets. Unlike conventional disinformation campaigns, these operations weaponize real information, aligning with the concept of "malinformation." State-sponsored hackers play a critical role by introducing "tainted leaks" (Hulcoop, A., Scott-Railton, J., Tanchak, P., Brooks, M., & Deibert, R. (2017). Tainted leaks: Disinformation and phishing with a Russian nexus. The Citizen Lab, Munk School of Global Affairs & Public Policy & University of Toronto. ) that blend genuine and falsified content to deceive the public. Journalists face ethical challenges when covering such leaks, as they must balance public interest with the risk of amplifying malicious agendas. In essence, hack-and-leak operations threaten journalistic credibility, information integrity, and democratic processes. By exploiting the perceived "authenticity" of leaked materials, these operations erode trust in media and public institutions. This essay underscores the importance of understanding the nuanced relationship between "real" and "fake" in leak-driven disinformation, highlighting the need for strategies to mitigate their broader impact on the digital public sphere.